Literary Studies Implementation of Religious Character Education for Elementary School Student: Studi Literatur Implementasi Pendidikan Karakter Religius Siswa Sekolah Dasar - Lela Indah Kristanti; Feri Tirtoni (Academia Open, 2021)
Character education is an attempt to instill the values of students behavior. Through character education can help in the formation of student character with the efforts made jointly between students,teachers and parents. This thesis aims to determine the implementation of religious character education for elementary school students in terms of the implementation process. The research method used is the study of literature or literature by using critical study methods. Data collection is done through literature data in the form of books, articles, relevant research journals. The result of the analysis obtained in this study are the process of implementing students religious character education through a learning process carried out by implementing student character building which is integrated in the subject. And through school culture which includes habituation and example.